Adaptive decode-and-forward protocol-based cooperative spectrum sensing in cognitive radio. (25th February 2015) - De, Chanchal Kumar; Kundu, Sumit
In this paper, a multiple-user cooperative spectrum sensing (MCSS) scheme based on a hybrid relay protocol is proposed to achieve the spatial diversity gains in detection of primary user in a cognitive radio (CR) networks. The proposed hybrid relay protocol (adaptive decode-and-forward protocol) works adaptively uses either AF or DF mode of relay operation. Closed-form expressions of detection probability ( Pd ) and false alarm probability ( a ) for the proposed adaptive decode-and-forward-based multiple-user cooperative spectrum scheme (ADF-MCSS) over Rayleigh fading sensing channels are derived. We extend the concept of two user amplify-and-forward (AF) and decode-and-forward (DF) cooperative spectrum sensing schemes in multi-users scenario (i.e., AF-MCSS and DF-MCSS) over Rayleigh fading channels. Closed-form expressions of AF-MCSS and DF-MCSS schemes over a Rayleigh fading channels are also evaluated and compared with that of proposed ADF-MCSS. Our analytical as well as simulation results demonstrate the impact of number of cooperative relays, SNR in sensing channel, false alarm on detection probability in proposed ADF and conventional AF or DF schemes.